Membangun Kembali Aceh: Reinvigorasi Syariat Islam Pasca Mahkamah Syariah - Agus Triyanta (Jurnal Hukum IUS QUIA IUSTUM, 2005)
Reconstruction of Aceh Darussalam as a potential momentum to strengthen the application of Islamic Syariah is significant, because Islamic Syariah as a legal system relates to law enforcement It includes three aspects such as state apparatus, substantial law, and development of legal culture.